Comparison of exit site infection and peritonitis incidences between povidone-iodine and normal saline use for chronic exit site care in peritoneal dialysis patients - Su Mi Lee; Hwa Seong Nam; Eu Gene Jeong; Young Ki Son; Seong Eun Kim; Won Suk An (The Korean Society of Nephrology, 2014)
Background: Catheter-related exit site infection is a major risk factor for the development of peritonitis and can contribute to failure of treatment maintenance in peritoneal dialysis (PD) patients. Although povidone-iodine can be used for exit site care, the irritation induced by the local application of povidone-iodine could lead to secondary infection. Therefore, we evaluated the clinical effectiveness of normal saline compared with povidone-iodine as a method of exit site care in chronic PD patients. Methods: In all, 126 patients undergoing PD treatment for>6 months between January 2006 and December 2009 were enrolled. Data were retrospectively analyzed for the incidence of exit site infection and peritonitis for 2 years prior to and after December 2007. In addition, we identified the incidences of catheter-related infections during follow-ups from January 2010 to December 2013. Results: The participants׳ mean age was 58.8±12.9 years. The incidences of exit site infection and peritonitis were one episode per 64.6 patients-months and one episode per 40.4 patients-months in the povidone-iodine group, respectively, whereas these were one episode per 57.5 patients-months and one episode per 45.6 patients-months in the normal saline group, respectively. Whereas Gram-positive bacteria most frequently caused catheter-related infections in both groups, culture-negative infections were dominant in the normal saline group. Conclusion: Exit site care using normal saline did not increase the incidence of exit site infection and peritonitis. Therefore, normal saline may be an alternative treatment for exit site care in patients receiving PD.